The Implementation of New Student Admissions for the Zoning System in Tarakan - Emma Juwita Magdalena Sirait; Suprianto Suprianto; Sitti Hardiyanti Arhas (Jurnal Office, 2021)
Admission of new students aims to ensure the acceptance of new students runs objectively, accountably, transparently, and without discrimination so as to encourage increased access to educational services. This study aims to determine the implementation of the acceptance of new zoning system students in the city of Tarakan in 2017. This study is a qualitative study, supporting instruments in this study are interview guidelines, observation guidelines, and document study guidelines. The main informants in this study were the Head of the Education Officer, the Head of the Education Officer, the Head of the UPT High School in North Kalimantan Province, the Head of the High School Supervisor of North Kalimantan Province. While the usual informants in this study were all the heads of UPT Education in Tarakan City Regency and other parties who were considered to know the problems in this study. Data collection techniques used were observation, interviews, and documentation. The data analysis technique used is data reduction, data display, and drawing conclusions. Based on the results of the study it was found that using a computerized system that determines the amount of quota through the poor family path, achievement path, reionization path, regular track, and out of town path.